Řešení konfliktů ve firmě - Tokošová, Irena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato bakalářská práce analyzuje interpersonální, tzn. mezilidské konflikty v podniku. Zaměřuje se především na řešení a předcházení konfliktů mezi zaměstnanci, zaměstnanci a klienty a mezi nadřízenými a podřízenými. Obsahuje návrhy řešení týkající se zlepšení mezilidských a pracovních vztahů v podniku.

This bachelor’s thesis analyses interpersonal conflicts in the company. This work is concentrated mainly on the conflicts resolution and prevention between employees, between employees and clients, between directors and employees. It includes the proposals of resolution which will leads to better interhuman and industrial relations in the company.
Conflict Resolution in The Company
Keywords: interpersonální konflikty; řešení konfliktů; řízení konfliktů; Plamínek; management; Čakrt Michal; vztahy pracovní; osobní konflikty; pracovní konflikty; mobbing; interpersonal conflicts; conflicts resolution; conflicts controls; Plamínek; management; Čakrt Michal; industrial relations; personal conflicts; work conflicts; mobbing